Efektifitas Pendidikan Kesehatan Metode Audio Visual Terhadap Pengetahuan Remaja Putri Tentang Vulva Hygiene - Jamiati; Dwi Elka Fitri (HEALTH CARE : JURNAL KESEHATAN, 2020)
The lack of knowledge of young women about vulva hygiene can be one of the triggers for vaginal discharge, this knowledge includes bad defecation (BAB) and urination (BAK) behavior. Reproductive health problems are a vital problem for building and maintaining women's health, however, the solution cannot be solved by curative efforts alone, so preventive efforts are prioritized. Health education is the right effort to increase adolescent knowledge about vulva hygiene. Audiovisual method can be used very well for health education for adolescents, because it is easier to understand and interesting. The purpose of this study was to determine the effectiveness of audiovisual health education methods. This is a pre-experimental research with two groups. The technique used in this research is purposive sampling technique. The results of this study indicate that the mean pre-test is 83.25 and the mean post-test is 98.50. From the results of this study it can be concluded that the provision of health education through audio-visual methods is effective in increasing the knowledge of young women about vulva hygiene at MAN 1 Indragiri Hilir. From the results of this study, it is hoped that this can be used as a guideline for respondents in their daily life, especially for the health of their reproductive organs, and that respondents will also be more familiar with the dangers of not practicing vulva hygiene properly. For health workers, it is hoped that they can use audiovisual media in the implementation of health education.